Activity Approach to Reflection of Ideas Formats of Thinking - Urozov Shahobiddin Ziyadullayevich (Research Parks Publishers, 2022)
The article focuses on the enrichment of modern science and philosophy with new concepts, ideas and approaches, the content of such concepts as